The Role of Feeling Trusted on Employee Engagement and Knowledge Sharing Behavior in Post-Acquisition Enterprises: A Pilot Study - Almadana, Aulia Vidya; Suharnomo, Suharnomo; Surya Perdhana, Mirwan (CV. Ridwan Publisher, 2021)
The acquisition is one of several company strategies to grow and develop. However, it has consequences on changes in the structure of the company and employees. The cultural collision and downsizing issues as consequences between two or more organizations involved in the acquisition process tend to give negative responses within the work environment. Whereas, to succeed in the acquisition process needed a positive environment that has an impact on good employee engagement further increasing knowledge sharing behavior among employees. Furthermore, feeling trusted among employees plays an important role because it leads feeling of justice, encouragement, and determines to what extent the employee has behaved in sharing knowledge. Hence, the aim of the present pilot study determines the validity, suitability, and reliability of a research instrument in preparation for a large scales study to examine the role of feeling trusted on employee engagement and knowledge sharing behavior in post-acquisition enterprises